Pollution Characteristics and Possible Sources of Seldom Monitored Trace Elements in Surface Sediments Collected from Three Gorges Reservoir, China - Bo Gao; Xin Wei; Huaidong Zhou; Jin Lu; Hong Hao; Xiaohong Wan (The Scientific World Journal)
A geochemical study of Three Gorges Reservoir (TGR) sediments was carried out to analyze the concentrations, distribution, accumulation, and potential sources of the seldom monitored trace elements (SMTEs). The mean concentrations of Li, B, Be, Bi, V, Co, Ga, Sn, Sb, and Tl were 47.08, 2.47, 59.15, 0.50, 119.20, 17.83, 30.31, 3.25, 4.14, and 0.58 mg/kg, respectively. The concentrations of total SMTEs, together with their spatial distribution, showed that the SMTEs were mainly due to anthropogenic inputs in the region of TGR. The assessment by Geoaccumulation Index indicates that Tl, Be, V, Co, and Fe are at the unpolluted level; Bi, Li, Ga, and Sn were at the “uncontaminated to moderately contaminated” level. However, B was classified as “moderately contaminated” level and Sb was ranked as “strongly contaminated” level. The pollution level of the SMTEs is Sb > B > Bi > Li > Ga > Sn > Tl > Be > V > Co > Fe. The results of Correlation Analysis and Principal Component Analysis indicated Be, V, Co, Ga, Sn, Tl, Bi, and Fe in sediments have a natural source. B and Li were positively correlated with each other and mainly attributed into similar anthropogenic input. In addition, Sb has less relationship with other SMTEs, indicating that Sb has another kind of anthropogenic source.